Sosialisasi Pentingnya Gizi Seimbang dan Pola Asuh Anak Sebagai Upaya Pencegahan Stunting di Desa Randuwatang - Nasrulloh, Muhammad Farid; Safitri, Rizka Aulia; Khuzaini, Nanang; Hidayatulloh, Faisol; Zuhriawan, Muhammad Qoyum (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2024)
The incidence of short toddlers or commonly known as stunting is one of the nutritional problems experienced by toddlers in the world today. Stunting is a condition of failure to grow in children under five years old as a result of chronic malnutrition, so that the child is too short for his age. The problem of stunting has a quite serious impact on the quality of human resources, especially the educational aspect. This impact is not only limited to academic achievement, but also to other aspects such as learning motivation, social abilities and the child's future. According to data from the Jombang District Health Service, in 2023 there will be approximately 534 toddlers experiencing stunting spread across all regions in Jombang Regency. Based on this explanation, community service in Randuwatang village through community service activities in the field of education took the initiative to implement a balanced nutrition socialization work program as an effort to prevent stunting, especially regarding its prevention. The method for implementing this socialization program consists of several strategic steps designed to ensure the effectiveness of activities in increasing public understanding of the importance of balanced nutrition and appropriate parenting patterns to prevent stunting. Community approach: Service implementers will start by coordinating with community leaders, village heads and posyandu cadres in Randuwatang Village. Based on the results and discussion of the implementation of community service activities with the socialization of "The Importance of Balanced Nutrition and Parenting as an Effort to Prevent Stunting" in Randuwatang Village, it was concluded that the socialization activities succeeded in increasing the community's knowledge and understanding by 80% about the importance of balanced nutrition and the dangers of stunting.